Determinan Kejadian Malaria di Wilayah Sulawesi - Junus Widjaja; Phetisya Pamela Frederika Sumolang; Made Agus Nurjana (ASPIRATOR - Journal of Vector-borne Disease Studies, 2016)
Indonesia is one of the countries in the world with high risk of malaria. Out of 496 districts in Indonesia, 396 districts is a malaria endemic area. 45% of the populations live in malaria endemic areas, such as the region of Sulawesi. This study aimed to determine the determinant for incidence of malaria in Sulawesi. Riskesdas data that have been implemented by the Agency for Health Research and Development in 2013 used in further analysis. The variables analyzed are characteristics, housing conditions, and the environment associated with the incidence of malaria. Data were analyzed by logistic regression. The results showed that there was a significant relationship between malaria by gender, education, occupation, home status, number of household members, window of the bedroom, the cleanliness of the dining room, ventilation of the living room, the type of floor in the house, house walls, ceilings, lighting source and taking preventive medication. The variables that most influence on the incidence of malaria in the region of Sulawesi is a type of home lighting. Integrated planning activities with relevant sectors, education about healthy homes and the restoration of housing through increased participation of the people needs to be done.